An assignment writing crash course: Transferring writing centre practice into the academic literacy classroom by reshaping the curriculum - Sparks, Linda; Norval, Gawain; Mpapela, Siwapiwe (Journal for Language Teaching, 2025)
The transfer of academic literacy (AL) skills into discipline-specific modules is one of the primary goals of AL interventions. Skills transfer entails students being able to read and write at academically appropriate levels, especially with regards to assignment writing. Previous research indicates that it takes time to teach AL skills, yet content modules require these skills almost instantly for successful assignment writing. Ultimately, this means that students are often underprepared for the writing tasks required in content modules at first-year level to the extent that it worsens the attrition rate. Thus, students may not obtain the necessary competencies in both writing skills and subject content. Therefore, the aim of this article is to seek a remedy for this adverse effect with the facilitation of a writing centre ‘crash course’ workshop in the AL classroom at the time students start writing assignments in core modules. The crash course focused on providing students with academic writing skills for assignment writing in their disciplines by combining writing centre pedagogy and social constructivist teaching strategies. Thus, the article measures the impact of the crash course by analysing both quantitative and qualitative data based on analyses of marks and students’ perceptions.